Discourse Analysis Study on the Determination of Marriage Dispensation in Religious Courts - Hasriana Usman; Rahmawati; Muh. Thayyib Kaddase (Universitas Islam Negeri Palopo, 2025)
This study examines the phenomenon of the determination of marriage dispensation in the Belopa Religious Court, Luwu Regency through a critical discourse analysis approach. The purpose of this study is to analyze the discourse structure, discursive practices, and socio-cultural practices that underlie the determination of marriage dispensation. The research method uses a qualitative approach with data collection techniques in the form of document studies on the determination of marriage dispensation in 2020-2023, in-depth interviews with judges, and observations of the trial process. The results of the study show that the discourse structure in the determination of marriage dispensation is dominated by considerations of benefit and prevention of harm, which is reflected in the use of Islamic legal diction and arguments. Discursive practices show the existence of a power relationship between the court authority and the applicant for dispensation, where the court has the legitimacy to determine the eligibility of underage marriage. Meanwhile, at the level of socio-cultural practice, the determination of marriage dispensation cannot be separated from the social construction of the Luwu community regarding marriage and adulthood, as well as economic and educational factors. This study concludes that the discourse of marriage dispensation in the Belopa Religious Court is the result of a complex interaction between legal authority, religious values, and the socio-cultural realities of the local community.